Advanced Alveolar Soft Part Sarcoma Treated with Pazopanib over Three Years. (26th October 2017) - Shido, Yoji; Matsuyama, Yukihiro
Abstract : Alveolar soft part sarcoma (ASPS) is a rare malignant tumor that generally occurs in adolescents and young adults. It progresses slowly, but lung and brain metastases often occur in the early phase of the clinical course, and chemotherapy has been reported as not being effective for ASPS. Pazopanib is a multitargeted tyrosine kinase inhibitor that has been clinically available from November 2012 in Japan. This is a case report of a patient presented with multiple lung metastases and unresectable primary abdominal ASPS. We initially treated this patient by systemic chemotherapy with combination use of ifosfamide and doxorubicin. Stable disease was observed without any objective response. Then, we finally started to administrate pazopanib 800 mg/day. After 25 months of pazopanib administration, slight tumor reduction and a decrease of enhancement were observed. Objective responses were achieved for both the primary tumor and metastatic lung tumor; however, a newly developed brain metastasis was subsequently identified. Based on this case, pazopanib appears effective against ASPS, except for brain metastases. This case suggests that pazopanib may be useful as a first-line drug against unresectable ASPS and that longitudinal assessment of brain metastasis should be performed in similar cases.